Zinc Oxide Inhibits Dental Discoloration Caused by White Mineral Trioxide Aggregate Angelus - Marciano, Marina Angélica; Camilleri, Josette; Costa, Reginaldo Mendonça; Matsumoto, Mariza Akemi [UNESP]; Guimarães, Bruno Martini; Duarte, Marco Antonio Hungaro (Elsevier, 2017)
Introduction The aim of the study was to investigate the addition of variable amounts of zinc oxide to inhibit dental discoloration caused by mineral trioxide aggregate (MTA) Angelus. Methods MTA Angelus and MTA with additions of 5%, 15%, and 45% zinc oxide (ZnO) in weight were tested. The set cements were characterized by using a combination of scanning electron microscopy, energy dispersive spectroscopy, and x-ray diffraction. Radiopacity and setting time were analyzed according to American National Standards Institute/American Dental Association (57/2012) and American Society for Testing and Materials (C266-08). Volume change was evaluated by using micro–computed tomography analysis. The pH and calcium ion release were measured after 3 hours, 24 hours, and 28 days. Dental discoloration in contact with the cements was measured after 24 hours, 28 days, and 90 days. Biocompatibility to subcutaneous implantation in rats was verified after 30 and 60 days. Results Addition of ZnO did not alter significantly the radiopacity, setting time, volume change, pH, and biocompatibility compared with MTA Angelus (P >.05). Calcium ion release increased with addition of ZnO (P <.05). Proportions of 15% and 45% ZnO interfered in hydration. The 5% ZnO addition was sufficient to prevent the dental discoloration observed with MTA Angelus. Conclusions The addition of 5%, 15%, or 45% zinc oxide to MTA Angelus inhibits dental discoloration without modifying the radiopacity, setting time, volume change, pH, and biocompatibility.
Keywords: Biocompatibility; biomaterials; cement; endodontics; materials science; surface chemistry/properties